ANALISIS MAJAS DALAM LIRIK LAGU â€œKU KIRA KAU RUMAHâ€ KARYA AMIGDALA - nadhifah, rifa nurul (IKIP Siliwangi, 2020)
This article aims to discover and figure of speech to describe what just what is contained in the lyrics of the song